The use of methyl ricinoleate in lactone production by Yarrowia lipolytica : aspects of bioprocess operation that influence the overall performance - Gomes, Nelma (2010)
Yarrowia lipolytica was used to produce γ-decalactone by the degradation of methyl ricinoleate (MR). A new method for inoculating the biotransformation medium was tested, which avoided the laborious step of washing cells from the growth medium. The consequent cell hydrophobicity increase led to an enhancement of aroma production. In a study of MR concentration in shake flasks, the highest productivity (15 mg L−1 h−1) was achieved using 30 g MR L−1. Lipase and protease activities were induced but no correlation between lipase induction and aroma production was found. The effects of different aeration and agitation rates were studied in bioreactor assays. Productivity was improved to 87 mg L−1 h−1, and another compound, 3-hydroxy-γ-decalactone, was detected in large amounts. Dehydration of this lactone produced two decenolides with aroma characteristics. The direct influence of oxygen on the production of both lactones was demonstrated.